Inspired by Malaysian batik / Ahmad Fikri Hakimi Ahmad Ghazali - Ahmad Ghazali, Ahmad Fikri Hakimi (2022)
This is Bulky hinge bracelet heavily inspired by Malaysian batik, giving a traditional pattern a fresh look matching the concept of modern contemporary.